Slitrk Missense Mutations Associated with Neuropsychiatric Disorders Distinctively Impair Slitrk Trafficking and Synapse Formation - Kang, Hyeyeon; Han, Kyung Ah; Won, Seoung Youn; Kim, Ho Min; Lee, Young-Ho; Ko, Jaewon; Um, Ji Won (Frontiers in Molecular Neuroscience, 2016)
Slitrks are a six-member family of synapse organizers that control excitatory and inhibitory synapse formation by forming trans-synaptic adhesions with LAR receptor protein tyrosine phosphatases (PTPs). Intriguingly, genetic mutations of Slitrks have been associated with a multitude of neuropsychiatric disorders. However, nothing is known about the neuronal and synaptic consequences of these mutations. Here, we report the structural and functional effects on synapses of various rare de novo mutations identified in patients with schizophrenia or Tourette syndrome. A number of single amino acid substitutions in Slitrk1 (N400I or T418S) or Slitrk4 (V206I or I578V) reduced their surface expression levels. These substitutions impaired glycosylation of Slitrks expressed in HEK293T cells, caused retention of Slitrks in the endoplasmic reticulum and cis-Golgi compartment in COS-7 cells and neurons, and abolished Slitrk binding to PTPδ. Furthermore, these substitutions eliminated the synapse-inducing activity of Slitrks, abolishing their functional effects on synapse density in cultured neurons. Strikingly, a valine-to-methionine mutation in Slitrk2 (V89M) compromised synapse formation activity in cultured neuron, without affecting surface transport, expression, or synapse-inducing activity in coculture assays. Similar deleterious effects were observed upon introduction of the corresponding valine-to-methionine mutation into Slitrk1 (V85M), suggesting that this conserved valine residue plays a key role in maintaining the synaptic functions of Slitrks. Collectively, these data indicate that inactivation of distinct cellular mechanisms caused by specific Slitrk dysfunctions may underlie Slitrk-associated neuropsychiatric disorders in humans, and provide a robust cellular readout for the development of knowledge-based therapies.